1992
DOI: 10.1111/j.1365-2621.1992.tb05513.x
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of High‐Methoxyl Pectin and Locust Bean Gum Solutions in Steady Shear

Abstract: The Cross and Carreau flow models described well the shear rateapparent viscosity data. The coil overlap parameter, c[q], correlated well with the zero-shear rate specific viscosities of these mixtures. Experimental values of intrinsic viscosities of the mixtures were in good agreement with the prediction based on an additive model of the individual contributions of the gums. From the results obtained for the mixtures of both polysaccharide solutions at similar viscosity, pH and ionic strength, no significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…At that time, the steady shear flow properties of prepared PBSG solutions were quantified at 20°C in shear rates of 0.1–300 s −1 . Shear stress ( τ )–shear rate (trueγ˙) data were fitted with the power law (Equation (1)), Carreau (Equation (2)), and Herschel–Bulkley (Equation (3)) models (Silva, Gonçalves, & Rao, ; Steffe, ):τ=knormalP(γ˙)nPη=η+η0ηfalse(1+false(λtrueγ˙false)2false)N…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At that time, the steady shear flow properties of prepared PBSG solutions were quantified at 20°C in shear rates of 0.1–300 s −1 . Shear stress ( τ )–shear rate (trueγ˙) data were fitted with the power law (Equation (1)), Carreau (Equation (2)), and Herschel–Bulkley (Equation (3)) models (Silva, Gonçalves, & Rao, ; Steffe, ):τ=knormalP(γ˙)nPη=η+η0ηfalse(1+false(λtrueγ˙false)2false)N…”
Section: Methodsmentioning
confidence: 99%
“…Shear stress (τ)-shear rate (̇) data were fitted with the power law (Equation (1)), Carreau (Equation (2)), and Herschel-Bulkley (Equation (3)) models (Silva, Gonçalves, & Rao, 1992;Steffe, 1996):…”
Section: Shear Dependencementioning
confidence: 99%
“…To make a 60 "Brix fructose, 1% pectin, 0.1 moles NaCl dispersion, first crystalline NaCl (AR grade, Mallinckrodt, Paris, KY) (1.13 grams) was dissolved in sodium citrate buffer (0.05 M, 3.0 pH) (97.5 grams) under agitation followed by fructose (Crystar, A. E. Staley) (150.0 grams) at room temperature. NaCl was added to control ionic strength of each dispersion (da Silva et al, 1992). The mixture was then heated to 1002 1°C and the pectin (Genu Pectin, type BB, rapid set 150", Hercules Inc., Newark, DE) was (2.5g) added slowly.…”
Section: Methodsmentioning
confidence: 99%
“…RHEOLOGICAL behavior of high-methoxyl (HM) pectin/sugar dispersions has been studied using steady and dynamic shear (Chou and Kokini, 1987;da Silva et al, 1992) while that of gels has been studied using torsional creep (Kawabata, 1977), axial creep in a Pochettino-type geometry (Dahme, 1985), and stress relaxation after compression (Comby et al, 1986). In addition, gel strength (Oakenfull et al, 1989) and instrumental texture profile parameters (Rao et al, 1989) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In the control sample, the Ea value was higher than that in the beverages formulated with XG, CMC and AV, indicating a significant effect of temperature on viscosity [14,33,42,43]. Of the three components, only the XG concentration had a significant effect on Ea (p value<0.05), which may be caused by conformational changes that occur during heating gum affecting the viscosity of solutions [3,44].…”
Section: Rotational Testmentioning
confidence: 99%